The The Effectiveness of Siwaliparri Value-Based Group Guidance in Improving Students' Empathy - Muhammad Junaedi Mahyuddin; Handayani Sura; Ahmad Muliawan; Amien Wahyudi; Aisyah Suryani; Yusran Sahodding (Universitas PGRI Yogyakarta, 2026)
Modern dynamics have contributed to a significant decline in empathy among adolescents; however, the potential of local wisdom as a foundation for guidance and counseling interventions remains empirically under-explored, particularly in the context of Mandar culture. This study aims to examine the effectiveness of group guidance based on Siwaliparri values, a Mandar cultural concept emphasizing togetherness and equality, in enhancing student empathy. Employing a Pre-Experimental One-Group Pretest-Posttest design, the research involved eight students (N=8) from SMA Negeri 1 Majene, selected via simple random sampling based on low empathy score criteria. Data were collected using an Empathy Scale (30 items, a=0.80) and analyzed using a Paired Sample t-test. Results indicated a significant increase in students’ empathy, shifting from the “low” category (Mean=70.1, SD=6.4) to the “moderate” category (Mean=86.3, SD=5.2), with t = 10.645 and p <0.001. The effect size (Cohen’s d = 2.78) demonstrates a very large practical impact of the intervention. In conclusion, Siwaliparri-based interventions are highly effective in increasing empathy, offering a culturally responsive framework for school counselors in Mandar and similar cultural contexts to address the empathy crisis among adolescents while preserving Mandar’s local wisdom. Keywords: empathy, group guidance, local wisdom, siwaliparri